Chapter Two: Bibi - Mall, Shireen (WritingThreeSixty, 2018)
My leaf had fallen as they say, and the end was here and now. Never would I have dreamt it would come in this way but this is my Takdir (fate). A clean sun streamed through the steel framed windows of the ward on the 2nd floor of the Burn Unit at Tygerberg Hospital. It was all but quiet with the bustle of my offspring circling the bed, with sombre, shiny tear- stained faces. In a corner, like a sentry with a stopwatch, stood the monitor recording the last efforts of a heart worn threadbare. â€œHe is here,â€ I said to them, â€œThe old man, your father is hereâ€. Startled by that they all joined hands with me.